Water Empowerment and Conservation for Sustainable Ecotourism (The Case of Bali Jungle Camping) - Fajar Yualida Isti Koma (International Journal of Glocal Tourism, 2021)
Purpose: The purpose of this study was to determine the extent of water empowerment activities carried out by Bali Jungle Camping in Tabanan Regency, Indonesia, in order to establish sustainable ecotourism. Research methods: The study uses a qualitative descriptive method with data collection techniques of observation and documentation. Findings: Bali Jungle Camping has good natural potential to be developed into sustainable ecotourism. In its operation which lasted approximately 4 years, the development was carried out based on environmental sustainability and empowerment of the surrounding community. Implications: Bali Jungle Camping has made several efforts in empowering water but still has several task points towards sustainable ecotourism